Analysis of Legal and Political Discourse in Contemporary Times - Tapia Millán, María Alejandra; Ruiz Ariza, Diana Cristina; Rojas Porras, Yordy Esteban; Ordoñez Pardo, Luis Alfredo (DIXI, 2016)
Purpose: from the concern of the Italian philosopher Giorgio Agamben on the ethical, legal and political meaning of extermination, we advance towards the analysis of a new paradigm of modern political space in essence, determined by a type of exclusion that remains in force to the present day. Description: this overview will take up the concept of biopolitics in order to understand the device that allows the emergence of bare life within the political space, namely, the state of exception. Point of view: at this point of the article, reflction centers on the problem of the testimony of survivors from concentration camps, a place where there is paradoxically an alternate pathway to this kingdom between life and death imposed by the contemporary political discourse. Conclusions: the latter opens a horizon for the woman question as another form of establishing social bonds, for which psychoanalytical concepts will be taken up in order to understand the feminine logic and their incidence in subjective and social shaping.